Relations entre la qualité des interactions enseignante-enfants et le développement du raisonnement spatial des enfants de maternelle quatre ans à temps plein en milieu défavorisé - St-Jean, Charlaine; April, Johanne; Bigras, Nathalie; Maïano, Christophe; Dupuis Brouillette, Marilyn (Canadian Journal of Education/Revue canadienne de l’éducation, 2022)
The purpose of this article is to examine the predictive role of the quality of teacher-child interactions on the development of spatial reasoning in full-time kindergarten four-year-old children in underprivileged settings. The matched sample is made up, on the one hand, of 232 children (130 girls, 102 boys) aged 58.29 months (SD = 4.93), and eight teachers holding a baccalaureate, having in average 12.2 years of teaching experience in preschool (SD = 5.45). Multiple mixed-effect regression analyzes showed that dimensions and sub dimensions of the quality of teacher-child interactions significantly and positively predicted the subtests of the spatial reasoning. This study highlights the importance of improving the quality of interactions in order to promote the development of spatial reasoning in four-year-olds.